(untitled) - Pruden, Hank (New Jersey, 2007)
A behavioral finance framework for systems building that provides the structure for integrating and interpreting indicators organized along the key dimensions of price, time, volume, and sentiment. A pattern recognition plan for trading—the Wyckoff Method of chart reading and technical analysis—that contains a set of laws and principles, which can be used to interpret chart patterns and take action. A model of trader psychology that is essential to the management of your mental state—the Ten Tasks of Top Trading—as well as various methods that will allow you to effectively maintain or modify this state
Keywords: Stock price forecasting,Stocks,Futures,Speculation,Dự báo giá cổ phiếu,Cổ phiếu,Tương lai,Đầu cơ